5(x+7)+2=-4(x-3)-11

Simple and best practice solution for 5(x+7)+2=-4(x-3)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+7)+2=-4(x-3)-11 equation:


Simplifying
5(x + 7) + 2 = -4(x + -3) + -11

Reorder the terms:
5(7 + x) + 2 = -4(x + -3) + -11
(7 * 5 + x * 5) + 2 = -4(x + -3) + -11
(35 + 5x) + 2 = -4(x + -3) + -11

Reorder the terms:
35 + 2 + 5x = -4(x + -3) + -11

Combine like terms: 35 + 2 = 37
37 + 5x = -4(x + -3) + -11

Reorder the terms:
37 + 5x = -4(-3 + x) + -11
37 + 5x = (-3 * -4 + x * -4) + -11
37 + 5x = (12 + -4x) + -11

Reorder the terms:
37 + 5x = 12 + -11 + -4x

Combine like terms: 12 + -11 = 1
37 + 5x = 1 + -4x

Solving
37 + 5x = 1 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
37 + 5x + 4x = 1 + -4x + 4x

Combine like terms: 5x + 4x = 9x
37 + 9x = 1 + -4x + 4x

Combine like terms: -4x + 4x = 0
37 + 9x = 1 + 0
37 + 9x = 1

Add '-37' to each side of the equation.
37 + -37 + 9x = 1 + -37

Combine like terms: 37 + -37 = 0
0 + 9x = 1 + -37
9x = 1 + -37

Combine like terms: 1 + -37 = -36
9x = -36

Divide each side by '9'.
x = -4

Simplifying
x = -4

See similar equations:

| Log[4x+9]=5 | | 7(x-7)-5=25x-108 | | 75-9g= | | 13/15//7/10 | | 4v+20-4=34 | | Log(4x+9)=5 | | x+x*19.6=4280 | | -16t^2+10t+26=0 | | 12x^2+16=172 | | x/9=251 | | 6(x+4)-5[x-(2x-3)]= | | -2(x-3)+5=3(x+4)+8 | | 3=3+y*.08 | | X+19=45 | | 16x^4-x-1=0 | | 16-3*(8-3)*2/5 | | 7(x-7)+29=3(x-4) | | 2x+3y-5x= | | X+(-9)=-36 | | X^2-18x=5x^3 | | p^2+30p+225=0 | | 3x*2+5x-174=0 | | 12tttttttt/36tttttt | | 80+10logx=40 | | 3+5x=2x+18 | | Log(5x-4)=2findx | | (7/x-1/3)=(1/4) | | 3800+15x=3300+25x | | -9+6n=3(2n-2) | | 4x^2+bx-3=0 | | (2)*(2/4) | | x+25=85 |

Equations solver categories